PENGARUH SERTIFIKASI GURU TERHADAP KOMPETENSI PROFESIONAL DAN KINERJA GURU - Juniardi, Muhammad Aqil; Suci Yuniati (Guruku: Jurnal Pendidikan Profesi Guru, 2024)
This study aims to describe the effect of teacher certification on professional competence and teacher performance through a literature review. A literature review of existing research was conducted by gathering and evaluating various scholarly materials, including scientific journals, books, and academic articles. The findings demonstrate that teacher certification has a clear and substantial impact on both a teacher's professional skills and their effectiveness in the classroom. Teachers who have participated in the teacher certification program show improvements in pedagogical knowledge, teaching skills, and professionalism. Teacher performance also improved in terms of learning effectiveness and student learning outcomes.